Urbanization in Far-Western Region of Nepal - Bista, Govinda Singh (NUTA Journal, 2021)
Nepal is one of the developing countries of the world. Nepal's level of urbanization was low in terms of urban population and number of urban centers until 2011, but it has been increasing over the recent years. The rate of urban growth in the country has also been faster lately. The research work is mainly based on secondary data. In this context, this paper is concerned with urbanization in Far-western Region of Nepal. This paper is mainly focused on analysing the growth of urban population and centers, spatial pattern of urbanization, size of urban areas, ranking of urban areas of Far-Western Region utilizing data from the population census 1881 to 2011 and recent data which are published by Ministry of Federal Affairs and Local Development 2016 of Nepal. The urban population has increased from 71108 in 1981 to 1058305 in 2016 while the number of urban centers has increased from 2 to 25 in the study area. The level of urbanization in this region was 5.38% in 1881 and it became 43.77% in 2016. The urban growth and urbanization of the Far-western Region is at accelerating stage in the present time. It is notable that out of 9 districts of this region, Kailali and Kanchanpur which are located in the Terai region share 77.55% of total urban population. According to the data we can say Far-western Terai (Kailali and Kanchanpur districts) is the hub of Far-western's urbanization. The spatial pattern of urbanization is disproportionate in the study area.